An Approach for Behavioral Fingerprinting of P4 Programmable Switches - Saueressig, Matheus; Franco, Muriel F.; Scheid, Eder J.; Granville, Lisandro Z. (Anais da Escola Regional de Redes de Computadores (ERRC); 2023: Anais da XX Escola Regional de Redes de ComputadoresDO - 10.5753/errc.2023.915, 2023)
Behavioral Fingerprinting is a technique used to understand the behavior of devices, enabling a better understanding of their functionality and improved anomaly detection. This paper proposes a methodology for generating the behavioral fingerprint of programmable switches. The methodology outlines the process of selecting metrics for analysis, extracting data from them, and organizing the information to construct a behavioral fingerprint for a programmable device within a network.